PENGARUH UPAH, MODAL, BAHAN BAKU DAN TENAGA KERJA TERHADAP PRODUKSI INDUSTRI KERAJINAN KAYU DI KABUPATEN GIANYAR - Cahyadinata, Wayan Purwa; Darsana, Ida Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2018)
One strategy that can be used in encouraging the middle and small industry sectors is to increase the role of Micro Small and Medium Enterprises (MSMEs) and people's economy. The purpose of this study was to analyze the effects of wages, capital, raw materials and labor simultaneously and partially to production. This research was conducted on wood craft industry in Gianyar Regency. The number of samples used is 80 industrial units. This study uses primary data obtained through structured interviews, in-depth interviews and observations. The technique of anaslisis used is multiple linear regression. The results showed that wages, capital, raw materials and labor simultaneously have a positive and significant effect on the production of wood craft industry in Gianyar regency. Partially wages, capital, raw materials and labor have a positive and significant effect on the production of wood craft industry in Gianyar regency. These results indicate that the ups and downs of wages, capital, raw materials and labor used in the process of producing woodcraft crafts will have a significant impact on the production of handicrafts produced by the wood craft industry in Gianyar regency. Keywords: wages, capital, raw materials, and labor